Emotional Intelligence and Academic Performance in First-Year and Third-Year Promoted Medical Students: Emotional Intelligence and Academic Performance in Medical Students - Din, Mohi Ud; Ikram, Shahzaib; Aziz, Somayya; Khalid, Muhammad Usman; Rizwan, Faseeh Salman; Abdullah, Muhammad; Hafeez, Muhammad Umair (Pakistan Journal of Health Sciences, 2024)
Emotional intelligence association with academic performance is assessed as it may be linked to higher academic achievement and improved empathy. Objectives: To fill the gap in existing research by examining the relationship between emotional intelligence and academic performance among first-year and third-year medical students. Methods: An analytical cross-sectional study in a private medical college of Faisalabad was done from September 2022 to August 2023. The academic performance of medical students was measured using their recent professional examination results. The first- and third-year promoted students were invited to participate. Students filled online Google-generated questionnaire form. Data were examined using SPSS version 22.0. Pearson correlation was employed to measure the association between emotional intelligence and academics and an independent sample T-test was used to compare means between MBBS classes. Results: 176 medical students (84 first-year promoted and 92 third-year promoted) participated in this study. A weak positive correlation between last exam marks and emotional intelligence was observed with significant p-values between exam marks and self-awareness (0.25, p=0.001); self-management (0.02, p=0.005); social awareness (0.19, p=0.006) and relationship management (0.19, p=0.006). The mean of all four elements (Self-assessment, self-management, social awareness, and relationship management) of emotional intelligence was higher (17.47, 17.11, 17.36 and 17.46) in third-year promoted students than first-year promoted students (15.76, 15.61, 15.79 & 15.64) respectively. Conclusions: It was concluded that third-year promoted medical students found more emotionally intelligent performed better in their recent professional examination than first-year promoted medical students found weaker in emotional intelligence.